Effect of Chronic Social Stress on Endothelial Function of the Mesenteric Artery of Normotensive and Spontaneously Hypertensive Rats - Kaprinay B.; Bernatova I.; Sotnikova R. (Sciendo, 2016)
The aim of the work was to study the effect of chronic social stress induced by increased population density, "crowding stress" on blood pressure and endothelial function of arteries of male normotensive Wistar and spontaneously hypertensive (SHR) rats. Based on the results, we assume that social stress-induced reduction in endothelium-dependent relaxation and increased blood pressure of SHR rats is most likely associated with decreased bioavailability of nitric oxide.